CRISPR-Cas-mediated diagnostics. Issue 11 (November 2022) - Li, Luoxi; Shen, Guanwang; Wu, Min; Jiang, Jianxin; Xia, Qingyou; Lin, Ping
Abstract : An ideal molecular diagnostic method should be sensitive, specific, low cost, rapid, portable, and easy to operate. Traditional nucleic acid detection methods based mainly on PCR technology have not only high sensitivity and specificity, but also some limitations, such as the need for expensive equipment and skilled technicians, being both time and labor intensive, and difficult to implement in some regions. However, with the continuous development of CRISPR-Cas technology and its application in molecular diagnosis, new approaches have been used for the construction of molecular diagnostic systems. In this review, we discuss recent advances in CRISPR-based molecular diagnostic technologies and highlight the revolution they bring to the field of molecular diagnostics. Highlights: CRISPR-Cas-mediated diagnostics can detect various pathogens, cancer biomarkers, and SNPs with high specificity, speed, low cost, and portability. The combination of Cas proteins with biosensors, biochips, biomagnetic beads, isothermal amplification, lateral flow, protein aptamers, and other technologies has resulted in the development of new diagnostic methods. Multiplexed CRISPR nucleic acid detection systems complete the detection of 169 viruses for diagnosing different diseases in a single sample, with the help of microfluidic technology. CRISPR-mediated antibody diagnosis technology can recognize thousands of antibodies in a sample simultaneously. The potential of CRISPR-Cas biosensing technologies is inspiring researchers to develop next-generation diagnostics platforms.